Santiago Luzuriaga and his nobelas-komedias works in the archival holdings and bibliographic collections of Patrimonio Nacional - Fernández Fernández, Javier (Historia y Memoria de la Educación, 2020)
This paper presents the biography of Santiago Luzuriaga y Odria (1828-1904), a teacher from Navarre (Spain), who enjoyed a long professional career and was the father of the Spanish pedagogue Lorenzo Luzuriaga. Santiago Luzuriaga was the author of singular works, which he called nobelas-komedias, written after the Spanish Government agreed to start paying teachers’ salaries beginning in 1901. The Archivo General de Palacio (General Archive of the Royal Palace of Madrid) and the Real Biblioteca (Spanish Royal Library) preserve some of these nobelas-komedias, which feature the peculiarity of being written with a phonetic spelling. The author argued for the necessary transformation of writing for the purpose of achieving a greater economy of language. Finally, the paper includes a copy of El ermano del alkalde dedicated to King Alfonso XIII of Spain, which is currently in the Real Biblioteca.